Stewards of the market how the Federal Reserve made sense of the financial crisis - Abolafia, Mitchel (Harvard University Press, 2020)
"Mitchel Abolafia goes behind the scenes with the Federal Reserve's powerful Open Market Committee as it responded to the 2008-2009 financial crisis. Relying on verbatim transcripts of closed meetings, Abolafia shows how assumptions about self-correcting markets stymied the Fed and how its leaders came to embrace new ideas"--